Student Perspectives on Using Virtual Reality to Create Informal Connection and Engagement - Amber Dailey-Hebert (Park University, 2022)
Following the global pandemic, educators relied heavily on live videoconferencing options and online meeting spaces to host class in lieu of traditional, in-person classroom learning. Yet, exhaustion and Zoom fatigue fueled a lack of engagement in such online spaces, while simultaneously the need for more informal connection to support learners' emotional well-being emerged. This study aims to better understand how online learners perceive the use of virtual reality (VR) as an alternative platform to informally connect and engage with one another, and to ascertain the impact on their satisfaction and motivation for such engagement. Specifically, the investigation sought to examine participant perceptions of social presence felt, the ability to connect and exchange informally, and the impact on motivation, digital literacy, and satisfaction overall.